13th Central European Symposium on Pharmaceutical Technology - Bartosz Maciejewski; Bianka Jacyna-Maciejewska; Małgorzata Sznitowska (Polish Pharmaceutical Society, 2021)
On 16th - 18th September in Medical University of Gdańsk took place 13th Central European Symposium on Pharmaceutical Technology (CESPT). It was the first time when conference from this cycle took place in Poland. It was organized in so called hybrid form - which joins the conventional "in person" admittance with on-line transmission of presented content. The conference gathered participants from 18 countries. The content presented included 12 plenary lectures, as well as 9 short oral talks and a continuous poster session organized in the form of an internet forum. The conference proceedings book is available at the website www.cespt2021.org. On 16th - 18th September in Medical University of Gdańsk took place 13th Central European Symposium on Pharmaceutical Technology (CESPT). It was the first time when conference from this cycle took place in Poland. It was organized in so called hybrid form - which joins the conventional "in person" admittance with on-line transmission of presented content. The conference gathered participants from 18 countries. The content presented included 12 plenary lectures, as well as 9 short oral talks and a continuous poster session organized in the form of an internet forum. The conference proceedings book is available at the website www.cespt2021.org. On 16th - 18th September in Medical University of Gdańsk took place 13th Central European Symposium on Pharmaceutical Technology (CESPT). It was the first time when conference from this cycle took place in Poland. It was organized in so called hybrid form - which joins the conventional "in person" admittance with on-line transmission of presented content. The conference gathered participants from 18 countries. The content presented included 12 plenary lectures, as well as 9 short oral talks and a continuous poster session organized in the form of an internet forum. The conference proceedings book is available at the website www.cespt2021.org. On 16th - 18th September in Medical University of Gdańsk took place 13th Central European Symposium on Pharmaceutical Technology (CESPT). It was the first time when conference from this cycle took place in Poland. It was organized in so called hybrid form - which joins the conventional "in person" admittance with on-line transmission of presented content. The conference gathered participants from 18 countries. The content presented included 12 plenary lectures, as well as 9 short oral talks and a continuous poster session organized in the form of an internet forum. The conference proceedings book is available at the website www.cespt2021.org.